THE INFLUENCE OF CUSTOMER EXPERIENCE, CUSTOMER SATISFACTION AND CUSTOMER BONDING ON CUSTOMER LOYALTYON SKINTIFIC SKINCARE PRODUCTS IN LHOKSEUMAWE CITY - Adnan; Putri Faradila; Syamsul Bahri; Rahmaniar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine the influence of Customer Experience, Customer Satisfaction, Customer Bonding on consumer loyalty to Skintific Skincare Products (Case study of residents of Lhokseumawe City). The method used in sampling is non-probability sampling, accidental fiber sampling. With a total of 105 respondents. Primary data in this research was taken by interviewing and distributing questionnaires. The data analysis technique used is the multiple linear regression analysis method, Classic assumption test, Instrument Test (Validity and Reliability), hypothesis testing using the SPSS 26.0 program. The results of this test show simultaneously that Customer Experience, Customer Satisfaction, and Customer Bonding have a positive and significant effect on customer loyalty to Skintific Skincare products. Partially, each variable, namely Customer Experience, Customer Satisfaction and Customer Bonding, has a positive and significant effect on customer loyalty to Skintific Skincare products. The managerial implications in this research show that increasing Customer Experience, Customer Satisfaction, Customer Bonding, and customer loyalty to Skintific Skincare products. Scientific must continue to utilize these variables so that consumer loyalty increases. The higher the good customer experience with a product, the higher the customer loyalty to that product will be.